A comparison of the effectiveness of commercial and natural carbohydrate-electrolyte drinks - Lagowska, K.; Podgórski, T.; Celinska, E.; Wiertel, L.; Krysciak, J. (Science & Sports, 2017)
Objectives: The aim of this study was to compare a natural carbohydrate-electrolyte drink (ND), containing salt, banana, water, pineapple juice, lemon juice, and honey, with a commercially available sports drink (CD) in terms of their effectiveness at hydrating and their effects on the maintenance of blood glucose levels and changes in the level of biochemical parameters of the blood. Equipment and methods: The study involved 11 rowers with an average age of 18.0 ± 2.0 and an average of 3.8 ± 1.4 years training. Their basic anthropometric and fitness parameters were measured. Then, in two sessions two weeks apart, the subjects performed 80 min of exercise on a rowing ergometer, during which they were administered one of the two tested drinks. Their body weight and blood biochemical parameters (glucose, lactate, HTC, urea, CK, WBC, LYM, MON, GRA, and FRAP) were measured both before and after the exercise. Results: During the exercise with CD, a significant decrease in body weight was reported, while body weight increased during the test with ND. Increases were seen in lactate, CK, WBC, LYM, MON, and GRA after consumption of both drinks.